A new species el Orycteroxenus Zachvatkin from Cryptotis n. nigrescens (Acarina: Sarcoptiformes: Glycyphagidae) - Camerik, A. M. (1974)
A description and illustration of the hypopial nymph of Oryrteroxenu¡ panamensis, n. sp., are provided. This mite parasitizes the shrew Cryptotis nigrescens nigrescens. The genus Orycteroxenus Zachvatkin is reported from Middle America for the first time.